IMPLEMENTASI AUTOMATIC HAND SANITIZER/ANTI BACTERIA DALAM MASA COVID-19 DI DESA GUWANG SUKAWATI (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
This community service during the COVID-19 pandemic aims to reduce touching objects or equipment simultaneously and reduce the spread of the corona virus within the family. Observations were made in various places, including homes, markets, banjar halls, to nearby stalls, then the results of the observations showed that not everyone who went out or entered the place washed their hands. This is due to various factors, namely the far distance of hand washing and soap, lazy to wash hands, and also awkward to borrow a hand washing place. Guwang Village is one of the villages located in Gianyar district. For the village of Guwang, there are already residents who have been affected by COVID-19. To minimize the spread of the virus, one of them can be done by diligently washing hands and using Hand Sanitizer. So the Automatic Hand Sanitizer/Anti Bacteria Using Infrared Sensor and Arduino was designed as a hand sanitizer from bacteria without direct contact. This is an alternative in using Hand Sanitizer / Anti Bacteria so that prevention of the corona virus can be done by diligently washing hands without having to be afraid without touching. Implementation automatic hand sanitizer held in Br. Sakih, Guwang village, Sukawati. By using this tool, it really helps people in personal hygiene to keep themselves clean and healty.